2003
DOI: 10.1016/s0014-5793(03)01157-8
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin‐sensitive Gαi protein and ERK‐dependent pathways mediate ultrasound promotion of osteogenic transcription in human osteoblasts1

Abstract: Bone cells respond to mechanical stimulation via mechanoreceptors and convert biophysical stimulation into biochemical signals that alter gene expression and cellular adaptation. Pulsed acoustic energy treatment raises membrane potential and induces osteogenic activity. How membrane-bound osteoblast mechanoreceptors convert physical ultrasound (US) stimuli into osteogenic responses is not fully understood. We demonstrated that low-intensity pulsed US treatment (200-W Ws pulse, 1 kHz, 30 mW/cm 2 ) elevated Cbfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 46 publications
(61 reference statements)
5
55
0
1
Order By: Relevance
“…30 In addition, LIPUS was reported to increase osteocalcin mRNA expression in preosteoblastic cell line. 31 All these studies implied that ultrasound stimulated osteoblast, activated bone matrix formation and, finally, facilitated intramembranous ossification. Moreover, high cellularity and less mineralization at the early stage of consolidation might be in favor of LIPUS treatment.…”
Section: Discussionmentioning
confidence: 97%
“…30 In addition, LIPUS was reported to increase osteocalcin mRNA expression in preosteoblastic cell line. 31 All these studies implied that ultrasound stimulated osteoblast, activated bone matrix formation and, finally, facilitated intramembranous ossification. Moreover, high cellularity and less mineralization at the early stage of consolidation might be in favor of LIPUS treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In cultured human osteoblasts, ERK-1/2 blockade prevented shear-induced proliferation and matrix synthesis (43). Tenocytes appear to share elements of a load-sensing mechanism similar to osteoblasts and osteocytes; stretch-activated potassium and calcium channels, internal calcium release, interstitial ATP release, and gap junction signaling all play a role in the proliferative response to membrane deformation, substrate deformation, or fluid shear (43)(44)(45)(46)(47). In elongated tenocytes, proliferation and collagen synthesis in response to ex vivo loading of chicken flexor tendon could be blocked by a gap junction inhibitor (48).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that effective physical stimulation could induce a series of biological changes in osteoblasts, such as osteogenic effect (58,59), alteration of gene expression (44,60), and related signal pathway changes (44,61). The beneficial effects for enhanced osteoblast adhesion and migration may result from reorganization of actin cytoskeleton to a certain degree (23).…”
Section: Journal Of Biological Chemistry 26207mentioning
confidence: 99%